A favorable prognosis case of posttraumatic endophthalmitis possibly from the protective effect of previously implanted implantable collamer lens (ICLs) - Yifan Xu; Bingsheng Lou; Guofu Huang (American Journal of Ophthalmology Case Reports)
Purpose: To report a favorable prognosis case of post-traumatic endophthalmitis following Implantable Collamer Lens (ICLs) implantation. Observations: A 24-year-old male presented with pain, redness and sudden-onset monocular blurry vision in the left eye immediately following an open globe injury caused by an azalea branch, which subsequently developed into infectious endophthalmitis. Five days prior to presentation, he had undergone ICLs surgery for high myopia of −8.00D. The right eye was normal. In the left eye, the uncorrected visual acuity was hand movement, and there was no improvement in the best corrected visual acuity (BCVA). The intraocular pressure was 30.6 mmHg. We observed a corneal perforation at the 2 o'clock position and a traumatic iris coloboma at the 11 o'clock position. Severe inflammation was present in the anterior chamber, with fibrin, inflammatory cells, and significant exudate in the pupillary area, but inflammation in the posterior segment was mild. The referring physician at the local hospital observed the branch contacting the anterior surface of the ICL through the traumatic iris coloboma at the 11 o'clock position. On the presentation, significant exudation in front of the ICL made it difficult to directly observe the ICL and crystalline lens under the slit lamp. Subsequent examinations revealed no obvious damage to either the ICL or crystalline lens. Anterior chamber irrigation and intracameral vancomycin were performed and we found Gram-positive cocci and white blood cells in his aqueous humor samples. He received systemic and topical broad-spectrum antibiotic therapy combined with corticosteroid treatment for a total of 5 days. Pain and vision loss improved with the resolution of intraocular inflammation. Visual acuity improved to 1.0 on the third day of treatment and remained stable at the 3-month follow-up. Conclusions and importance: Here, we report a case of trauma-induced endophthalmitis with a favorable prognosis. The ICL played a crucial protective role by protecting the lens, thereby preventing potentially devastating outcomes, suggesting the need for increased clinical attention on this matter.